Microglial remodeling of actin network by Tau oligomers, via G protein-coupled purinergic receptor, P2Y12R-driven chemotaxis - Das, Rashmi; Chinnathambi, Subashchandrabose (Traffic, 2021)
Alzheimer's disease (AD) is associated with age-related neurodegeneration, synaptic deformation and chronic inflammation mediated by microglia and infiltrated macrophages in the brain. Tau oligomers can be released from damaged neurons via various mechanisms such as exosomes, neurotransmitter, membrane leakage etc. Microglia sense the extracellular Tau through several cell-surface receptors and mediate chemotaxis and phagocytosis. The purinergic receptor P2Y12R recently gained interest in neurodegeneration for neuro-glial communication and microglial chemotaxis towards the site of plaque deposition. To understand the effect of extracellular Tau oligomers in microglial migration, the P2Y12R-mediated actin remodeling, reorientation of tubulin network and rate of migration were studied in the presence of ATP. The extracellular Tau species directly interacted with P2Y12R and also induced this purinoceptor expression in microglia. Microglial P2Y12R colocalized with remodeled membrane-associated actin network as a component of migration in response to Tau oligomers. As an inducer of P2Y12R, ATP facilitated the localization of P2Y12R in lamellipodia and filopodia during accelerated microglial migration. The direct interaction of extracellular Tau oligomers with microglial P2Y12R would facilitate the signal transduction in both way, directional chemotaxis and receptor-mediated phagocytosis. These unprecedented findings emphasize that microglia can modulate the membrane-associated actin structure and incorporate P2Y12R to perceive the axis and rate of chemotaxis in Tauopathy.
Keywords: actin remodeling; Alzheimer' chemotaxis; microglia; migration; s disease; Tau Oligomers

Photodynamic sensitizers modulate cytoskeleton structural dynamics in neuronal cells - Dubey, Tushar; Chinnathambi, Subashchandrabose (Cytoskeleton, 2021)
The neuronal cytoskeleton plays a crucial role in maintaining cell integrity and functioning of neurons. Cytoskeleton deformities have been reported to be associated with neurodegenerative diseases thus; cytoskeleton can be targeted for therapeutic strategies. The therapeutic application of photosensitive molecule is termed as photodynamic therapy (PDT). PDT has been applied in the field of dermatology, cancer biology, and antimicrobial therapy. PDT induces several changes in cells, which include induction of apoptosis, DNA damage, and induction of inflammatory response. PDT has been also reported to modulate cytoskeleton such as actin dynamics. The in vitro studies suggested that PDT using dyes such as Toluidine Blue and Rose Bengal effectively modulated the actin cytoskeleton, neurite outgrowth, tubulin, and Tau aggregation. In this review, we focused on the effect of photosensitized molecules on various cytoskeleton proteins. We hypothesize that PDT could have potency against Alzheimer's disease and other neurodegenerative disorders.
Keywords: Actin; Alzheimer' cytoskeleton modulation; neuronal cytoskeleton; photodynamic therapy; s disease; Tubulin